Living on Ice: Problems of Urban Development in Canada's North - French, Hugh (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1994)
Summary Canada is a cold country. It is only along the maritime low land fringes of the Pacific coast that snow and sub-freezing temperatures are rare. By contrast, those areas along the southern borders, where most of the Canadian population resides, are seasonally cold. In these regions, seasonal agriculture is possible, plant and animal productivity is high, and the constraints of cold can be temporarily forgotten during the summer months. Elsewhere, over the vast majority of the Canadian landmass,and certainly north of 60°N, the problems created by coldness persist throughout the year. Although there are few urban settlements in excess of 5000 people, these constraints dominate urban and socio-economic activities. The purpose of this paper is to illustrate the nature of such constraints, paying particular attention to the character of perennially frozen substrates (perma-frost), terrain disturbances caused by various types of construction activity, and problems associated with groundand surface waters.